2017
DOI: 10.1002/pen.24735
|View full text |Cite
|
Sign up to set email alerts
|

CdS impregnated cellulose nanocrystals/PVDF composite flexible and freestanding films: Impedance spectroscopic studies

Abstract: Nanocrystalline CdS impregnated cellulose nanocrystals (CdS‐Cellulose) were embedded in polyvinylidene fluoride (PVDF) matrix and free‐standing flexible films of CdS‐cellulose/PVDF nanocomposite were made by sol‐gel technique. Effect of CdS loadings in cellulose embedded in the host matrix (PVDF) on the impedance properties was studied critically for the above samples. Dielectric constants were studied as a function of frequencies (1–100 kHz) at room temperatures. The dielectric constant increased significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…[ 1‐5 ] In order to solve these problems, studies have been focused toward the employment of biodegradable materials in various applications such as packaging, automotive, textile, biomedical and agricultural industries. [ 6‐15 ] There are numerous kinds of biodegradable materials such as polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polyhydroxyalkanoates (PHA), and starch etc. [ 1,16‐19 ] Among these biodegradable materials, polylactic acid (PLA) is the most promising one to be used in all applications due to its biodegradability, competitive cost, and comparable properties with conventional petrochemical‐based plastics that is, stiffness, strength and gas permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1‐5 ] In order to solve these problems, studies have been focused toward the employment of biodegradable materials in various applications such as packaging, automotive, textile, biomedical and agricultural industries. [ 6‐15 ] There are numerous kinds of biodegradable materials such as polylactic acid (PLA), polybutylene adipate terephthalate (PBAT), polybutylene succinate (PBS), polyhydroxyalkanoates (PHA), and starch etc. [ 1,16‐19 ] Among these biodegradable materials, polylactic acid (PLA) is the most promising one to be used in all applications due to its biodegradability, competitive cost, and comparable properties with conventional petrochemical‐based plastics that is, stiffness, strength and gas permeability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 68,69 ] Moreover, it has a low thermal expansion coefficient, high aspect ratio, better tensile strength, and good mechanical and optical properties. [ 14,70,71 ] Thus, it has been used in many applications such as paper making, coating additives, food packaging, flexible screens, optically transparent films, lightweight materials for ballistic protection, and automobile windows. Besides, it also has potential in biopharmaceutical applications such as in drug delivery and for fabricating temporary implants.…”
Section: Introductionmentioning
confidence: 99%
“…This was due to its irregular surface roughness with high peaks (bumpy surface). Consequently, the electrons tend to move by tunnelling [44]. Figure 10b shows the log-log variation in σ ac as a function of frequency.…”
Section: Electrical Analysis Of the Pcm Materialsmentioning
confidence: 99%
“…It was found that an increase in cellulose content in polymer matrices noticeably improves the tensile strength of composite membranes [ 17 , 18 ]. Due to its renewable nature and biodegradability [ 19 ], cellulose is often impregnated into the polymer matrix of PVDF to enhance mechanical strength, as reported by studies [ 20 , 21 ]. The purest source of cellulose fibers, in addition to being the most environmentally and economically viable, is bacterial nanocellulose (BNC) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%